Takayasu Arteritis with Congestive Heart Failure in a 16-year-old Indian Male Child - Manisha Mehra; Poonam Joshi; Ankit Kumar Sahu; Surya Kant Tiwari (Journal of Indian College of Cardiology)
Takayasu arteritis (TA) is a rare inflammatory disease affecting medium- to large-sized vessels, notably the aorta and its branches, posing significant challenges due to arterial obstruction. We present the case of a 16-year-old Indian male with recurrent hospitalizations for congestive heart failure, eventually diagnosed with TA. Clinical examination revealed discrepancies in blood pressure, absent pulse in the left leg, and cardiovascular abnormalities. Laboratory findings indicated inflammation, and imaging confirmed arterial involvement. Treatment involved immunosuppressive therapy and symptomatic management. Despite diagnostic and therapeutic challenges, the patient showed improvement after 3 months. This case shows diverse clinical manifestations, diagnostic complexities, and the importance of a multidisciplinary approach to management. Further research is crucial in understanding mechanisms and optimizing therapeutic strategies for this rare vasculitis.